1978
DOI: 10.1007/bf01968614
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the spontaneous histamine release by adrenergic and cholinergic drugs

Abstract: Experiments have been reported on the possible modulation of the spontaneous histamine release by adrenergic and cholinergic drugs. Adrenergic drugs increase the spontaneous histamine release in vivo, and in neoplastic mast cells, in vitro. The mechanism of histamine release appears to be dependent upon the activation of alpha-adrenoceptors. Cholinergic drugs activate the release of histamine in many secretory processes in vivo; in vitro, acetylcholine is one of the most powerful histamine releasers in isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…In fact it is exocytotic, as shown by light and electron microscopy (Fantozzi et al 1978a(Fantozzi et al , 1978b; it is energy requiring, occurs at physiological pH, and needs calcium as well as sodium in the extracellular medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact it is exocytotic, as shown by light and electron microscopy (Fantozzi et al 1978a(Fantozzi et al , 1978b; it is energy requiring, occurs at physiological pH, and needs calcium as well as sodium in the extracellular medium.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies (Fantozzi et al 1978a;Fantozzi et al 1978b) have demonstrated that acetylcholine-induced histamine secretion requires intracellular and extracellular calcium. In the experiments presented in this paper, we have extended the study of ionic dependence of cholinergic histamine release to sodium and hydrogen ions, previously shown to influence the secretary response by various histaminereleasing agents, ATP, compound 48/80 and the ionophore X537 A (Mongar & Schild, 1958;Uvnis & Thon, 1961;Dahlquist, Diamant & Kruger, 1974;Hayashi, Ichikawa, Saito & Tomita, 1976;Kazimierczak, Patkar & Diamant, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in our laboratories have shown that exogenous acetylcholine causes the release of histamine from isolated rat serosal mast cells, featuring a sequential exocytotic process, dependent on metabolic energy, and upon the extracellular concentration of sodium, calcium and hydrogen ions (Fantozzi, Masini, Blandina, Mannaioni & Bani-Sacchi, 1978a;Fantozzi, Moroni, Masini, Blandina & Mannaioni, 1978b;Blandina, Fantozzi, Mannaioni & Masini, 1980). The secretion of histamine is preferentially evoked by muscarinic cholinergic agonists, and competitively blocked by atropine, indicating the participation of muscarinic receptors.…”
Section: Introductionmentioning
confidence: 91%
“…From these studies it has been shown that noradrenaline reduces the release of histamine from mast cells caused by antigens, dextran, acetylcholine or by the compound 48/80 (1,12). Acetylcholine, on the contrary, induces the release of histamine from mast cells (13) as do various neuropeptides (11,19,31).…”
mentioning
confidence: 99%